Assessing the Role of Climate Change in Desertification Processes - Haydarov Hasanjon Hakimovich; Kushimov Bakhtiyor Alishovich (Web of Journals Publishing, 2023)
This scientific article provides a comprehensive analysis of the role of climate change in desertification processes. It examines the impacts of climate change on various factors contributing to desertification, such as precipitation patterns, temperature changes, and land-use practices. The study utilizes a combination of literature analysis and methodology to investigate the relationship between climate change and desertification. The results highlight the significant influence of climate change on desertification processes, emphasizing the need for effective adaptation and mitigation strategies. The article concludes by discussing the implications of the findings and suggests future research directions.
Keywords: desertification, climate change, precipitation patterns, temperature changes, land-use practices, adaptation, mitigation, literature analysis, methodology.